(untitled) (International Journal of Engineering and Computer Science, 2022)
This article presents the analysis, design, simulation, construction and characterization of an axial radiation helical antenna with medium gain (11dBi) and circular polarization as a proposed use for the emergency water information network. Due to its application in the earth station, there are no dimensional limits. The parameters and results for an operating frequency of 915 MHz are presented.